In vivo effects of antibodies to immune response gene products: prevention of experimental allergic encephalitis. - Steinman, L (1981)
Prevention of experimental allergic encephalitis in SJL/J [H-2s] mice was achieved with in vivo administration of antibody reactive with I-As gene products prior to immunization with spinal cord antigen. No protection was evident in animals that received antisera specific for I-Js gene products. Administration of antibody to I-As beginning 5 days after immunization with spinal cord antigen delayed, but did not prevent, the onset of experimental allergic encephalitis.